Prostate-specific membrane antigen targeted organic semiconducting polymer nanoparticles for enhanced photothermal therapy of prostate cancer - Jiang, Zhongji; Zhang, Xun; Kadeerhan, Gaohaer; Zhang, Jin; Jin, Jiali; Hu, Weijing; Guo, Wenmin; Guo, Hong; Wang, Dongwen (Frontiers in Immunology, 2026)
Photothermal therapy (PTT) in the second near-infrared window (NIR-II, 1000–1700 nm) enables deep-tissue penetration and reduced off-target damage, offering a promising approach for localized cancer ablation. A major challenge, however, lies in achieving efficient and tumor-specific accumulation of photothermal agents. In this study, we developed a prostate-specific membrane antigen (PSMA)-targeted NIR-II photothermal nanoplatform based on an organic semiconducting polymer (OSP12). The OSP12 core was encapsulated with DSPE-PEG-Mal and covalently conjugated with ACUPA, a high-affinity PSMA ligand, to generate PSMA-OSP12 nanoparticles (NPs). These nanoparticles exhibited strong NIR-II fluorescence emission and high photothermal conversion efficiency under 808 nm excitation; notably, at 1.0 W/cm2 for 5 min the maximum solution temperature reached 77.3°C, and the particles showed excellent photothermal stability, retaining >90.0% of their peak heating performance after five on/off irradiation cycles. Owing to their enhanced targeting capability and robust photothermal stability, PSMA-OSP12 NPs enabled effective photothermal ablation of PSMA-positive prostate tumors with minimal systemic toxicity in vivo. Collectively, our findings demonstrate that PSMA-OSP12 NPs constitute a potent and precise NIR-II photothermal nanoplatform for prostate cancer treatment.